2017
DOI: 10.5430/irhe.v2n3p1
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Education Majors’ Basic Knowledge of U.S. Constitutional Rights and Pedagogical Implications

Abstract: University students in the United States preparing for a career in as teachers Pre-K -12 professional education must possess a basic understanding of constitutional law applicable to the profession. Undergraduate teacher education majors in their first course for teacher education majors participated in a survey research study designed to measure their confidence in ability to explain a relevant example of the 1 st , 4 th , 10 th , 14 th , and 15 th Amendments of the U.S. Constitution in the context of profess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…However, with respect to the general population in the U.S. and American undergraduate student knowledge at regional, public colleges and universities in particular, a gap exists in the scholarly literature regarding knowledge of the Bill of Rights among undergraduate students at regional public universities. The few studies on college students include Call and O'Brien (2011), who reported First Amendment knowledge of preservice teachers, Heuer and Coggins (2017), who reported knowledge of undergraduate criminal justice students on a select number of constitutional amendments, and likewise Coggins and Heuer (2017), who reported knowledge of undergraduate education students on a select group of constitutional amendments. In each of those three research studies, knowledge of only specific amendments from select populations of undergraduate students were investigated and reported.…”
Section: Introduce the Problemmentioning
confidence: 99%
“…However, with respect to the general population in the U.S. and American undergraduate student knowledge at regional, public colleges and universities in particular, a gap exists in the scholarly literature regarding knowledge of the Bill of Rights among undergraduate students at regional public universities. The few studies on college students include Call and O'Brien (2011), who reported First Amendment knowledge of preservice teachers, Heuer and Coggins (2017), who reported knowledge of undergraduate criminal justice students on a select number of constitutional amendments, and likewise Coggins and Heuer (2017), who reported knowledge of undergraduate education students on a select group of constitutional amendments. In each of those three research studies, knowledge of only specific amendments from select populations of undergraduate students were investigated and reported.…”
Section: Introduce the Problemmentioning
confidence: 99%